Media today : an introduction to mass communication - Turow, Joseph. 4 0 16; 5 (Boston : Houghton Mifflin Co., 1999)
How do books, newspapers, music recordings, movies, television shows, and online sites get made? How does content in different media get funded, produced and delivered to the right audiences? Why do certain materials and not others get created and distributed in different media? What role do governments (federal, state, local) play in the process? [This book] addresses these and related questions with concrete examples from a wide variety of mass media - from books to cable television, highway billboards to online services. The text tracks, among other developments, the explosion of competition among new and old media, pressures toward greater and greater conglomeratization among media firms, the need to increasing segment audiences, and their obligation to expand global sales. Students need to understand what is happening, why, and with what possible consequences for society. -Pref.
Understanding mass media: Understanding mass media, why should we care; Making sense of the media business; Government regulation, self-regulation, and ethics -- Print media: Print media, from past to present; Book industry; Newspaper industry; Magazine industry -- Electronic media: Rise of sound recordings and radio; Radio industry; Recording industry; Rise of motion pictures and television; Motion picture industry; Television industry; Computer software and on-line services -- Advertising and public relations: Rise of advertising and public relations; Advertising; Public relations --Conglomerates and cross-media activities: Understanding the big picture; Understanding cross-media strategies -- Mass media issues and effects: Mass media issues; Media issues in play -- Glossary.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Mass media. -- 20; 20; 2